Experimental investigation of steady state power balance in double null and single null H mode plasmas in MAST Upgrade - J. Lovell; S.S. Henderson; J.M. Stobbs; A. Kirk; F. Federici; B.S. Patel; P.J. Ryan; J.R. Harrison; B.A. Lomanowski; J.D. Lore (Nuclear Materials and Energy)
Global power balance calculations in steady state H mode plasmas varying the distance between separatrices (drsep) and the divertor configuration have been performed in MAST Upgrade. As drsep becomes more negative, more of the power crossing the separatrix goes to the lower divertor. The inner divertor receives a higher fraction of the power exhaust in a Super-X divertor plasma compared to a conventional divertor plasma at similar negative drsep, which is a concern for high power devices employing alternative divertor configurations for power exhaust handling. Global power accounting suggests >30% of the input power is unaccounted for with the power loss channels quantified in this work. Charge exchange and orbit losses from the NBI could account for a large fraction of unaccounted power but it is not possible to precisely determine this without further diagnostic calibration.